A sensitivity analysis of price formulae - J. J. Doppegieter; I. J. Lambrechts (South African Journal of Business Management, 1985)
This is the last in a series of four articles. In the first article two price formulae were discussed and in the subsequent two articles two methods of analysis were demonstrated. In this article a third method of analysis concerning the sensitivity of some selected model parameters is presented. Four parameters have been selected, i.e. the allowed profitability rate, the inflation rate, the growth rate, and the statutory tax rate. The value of each factor has been increased and decreased by 10% to test the sensitivity of each. In both price formulae the allowed profitability rate has the highest relative importance, followed by the inflation rate. Furthermore, in price formula A some parameters have no or only a small short-term effect on the internal rate of return, e.g. the statutory tax rate. In addition, the internal rate of return of formula A is generally more volatile to changes in the variables analysed than that of formula B. This type of analysis could be very helpful for negotiations between price/tariff-determining bodies and price-controlled undertakings/industries.
Keywords: 650